Rancang Bangun Sistem Monitoring Keamanan, Suhu dan Kelembapan Gudang Beras Menggunakan Bot Telegram Berbasis IoT - Zulfikar Aji Santoso; Imam Suharjo (Journal of Information System and Artificial Intelligence, 2024)
Rice is one of the staple foods that is an important commodity where rice consumption and production in Indonesia is very high. High temperature and humidity can cause rice to easily become damaged, for example the appearance of rice bugs, mold growth and an increase in the number of broken grains. In addition, the security of the rice warehouse must also be maintained to prevent losses such as theft. The purpose of this research is to create a system and tool that can monitor or maintain security, temperature and humidity in rice warehouses. The result of this research is a system and tool capable of maintaining temperatures below 30 degrees Celsius and also air humidity below 65% automatically. In addition, a picture of the situation in the warehouse will be sent via a special Telegram Bot to the user as a surveillance and warehouse security tool.